0428 DEPRESSION IS ASSOCIATED WITH DECREASED SLEEP QUALITY RATHER THAN RESPIRATORY DISTURBANCE OR HYPOXIA DURING SLEEP IN PATIENTS WITH OBSTRUCTIVE SLEEP APNEA. (28th April 2017) - LEE, S; Choi, J; Lee, Y; Jeong, D
Abstract: Introduction: Obstructive sleep apnea is known to be associated with depression, but which changes in OSA patients are responsible for the depression is still controversial. This study was conducted to examine which factors, including the severity of OSA, are associated with the depressive symptoms and excessive daytime sleepiness in OSA patients. Methods: We reviewed retrospectively the data of 1200 subjects (872 men; mean age 48.7 years) who completed self-report questionnaire and performed polysomnography in the center for sleep and chronobiology of SNUH. We compared Beck Depression Inventory (BDI) and Epworth Sleepiness Scale (ESS) score between control and OSA groups. The analyses for OSA subgroups classified by severity and partial correlation were performed. Results: The BDI score was significantly higher in OSA group than control group (12.3 ± 7.6 vs. 10.4 ± 6.2, p=0.002). There was significant difference in ESS score among mild, moderate and severe OSA subgroups (7.1 ± 4.8 vs. 8.1 ± 4.5 vs. 10.1 ± 4.5, p<0.001), but not in BDI score (13.4 ± 7.8 vs. 12.3 ± 8.1 vs. 11.5 ± 6.9, p=0.236). After adjusting for age, sex and BMI, BDI score in OSA group was significantly correlated with total sleep time (TST), sleep efficiency (SE), wake after sleep onset (WASO), and sleep latency (SL), but not with apnea-hypopnea index (AHI) and average O2 (r=-0.116, p <0.00; r=-0.001, p =0.001; r=0.077, p =0.014; r=0.127, p <0.001; r=-0.027, p=0.387; r=0.019, p=0.542, respectively). The ESS score in the OSA group was significantly correlated with TST, SE, WASO, SL, AHI and average O2 (r=0.114, p <0.001; r=0.109, p =0<0.001; r=-0.081, p =0.01; r=-0.138, p <0.001 and r=-0.134, p <0.001, respectively). Conclusion: In current study, patients with OSA showed higher depressive symptoms than those without OSA. Daytime sleepiness in OSA patients was associated with the severity of OSA as well as sleep architectures. However, depressive symptom was associated with only sleep architectures, but not with the severity of OSA. Depression in OSA patients may be explained better by sleep quality rather than respiratory disturbance or hypoxia during sleep. Support (If Any):